MODIFIKASI PERMAINAN SOFTBALL UNTUK SISWA SEKOLAH DASAR - Sridadi Sridadi (Jurnal Pendidikan Jasmani Indonesia, 2009)
Softball is a team sport modified from baseball which have been developed and popular in the USA. It is a modified games since it could previously be played by male. George Hancock was the one who started to modify baseball with the purpose was to make the game was playable in the winter by establishing written rules named indoor baseball. The effort to socialize this game to children should be done as early as possible. Elementary school is a good starting point to introduce this games. Through school physical education, children can be introduced by various games in order to enrich student movement. One of the effort is to provide modified softball. Several problems which will be explore are why softwall needs to be modified, what is the advantage of the modification, and what are the modified forms of softball? Kata kunci: Modifikasi, Softball, Sekolah Dasar